Realisasi Tindak Ekspresif Dalam Pidato Di Kalangan Siswa Kelas X SMA Negeri I Geyer - Setyaningrum, Dewi, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
This research the purpose to know type of speech acts expressive and strategies speech acts expressive on speech student class X SMA Negeri 1Geyer. Data collection that used is observation. Mechanical validity is triangulation technique. Based on research can be two conclusions: (1) was found threeteen speech acts expressive on speech students is: type of speech acts expressive respect, type of speech acts expressive gratitude, type of speech acts expressive praise, type of speech acts expressive blame, type of speech acts expressive suspect, type of speech acts expressive accused, type of speech acts expressive admit, type of speech acts expressive gratitude, type of speech acts expressive quipped, type of speech acts expressive apologize, type of speech acts expressive insulting, type of speech acts expressive mocking and expressive speech acts criticize. And (2) direct strategies and indirect stategies that found in research are: direct strategy in this research is found in the 13 type strategies direct speech acts expressive respect, 9 type a direct strategy of speech acts expressive of gratitude, 11 type a direct strategy of praise, 4 type a direct strategy of blame, 2 type a direct strategies of suspect, 2 type a direct strategies accused, 13 type a direct strategies admit, 6 type a direct strategy grateful, 11 type a direct strategy apologize, 3 type a direct strategy of insulting, 1 type a direct strategy of mocking and 8 type a direct strategy of criticized. While indirect strategy that is found in speech students class X is a 6 typ indirect strategy of blame, 1 type suspect, 2 type indirect strategy mocking, and 7 type indirect strategy quipped. Keyword: expressive speech act, speech act strategies direct, indirect speech act strategies